2002
DOI: 10.1088/0031-9155/47/10/401
|View full text |Cite
|
Sign up to set email alerts
|

First imaging results obtained with a multimodal apparatus combining low-field (35.7 mT) MRI and pulsed EPRI

Abstract: Nuclear magnetic resonance imaging (MRI) provides excellent images of organs and is an essential diagnostic tool in the medical field. Electron paramagnetic resonance imaging (EPRI) is being increasingly used in the biomedical field because of recent hardware advances. We present the first images obtained with a low-field (35.7 mT) multimodal apparatus that combines MRI and pulsed EPRI. For this purpose, the sample is composed of two sections, one sensitive to MRI and the other sensitive to EPRI. The MRI secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The resonator system is simple and easy to implement. The MCPGRs used here are more efficient at generating an RF magnetic field than the composite resonator system previously reported [8,9,26]. The MCPGR for EPR was 2-fold more efficient than the bridged LGR used in a composite resonator; the MCPGR for NMR was 10-fold more efficient than the solenoidal coil used in a composite resonator [26].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The resonator system is simple and easy to implement. The MCPGRs used here are more efficient at generating an RF magnetic field than the composite resonator system previously reported [8,9,26]. The MCPGR for EPR was 2-fold more efficient than the bridged LGR used in a composite resonator; the MCPGR for NMR was 10-fold more efficient than the solenoidal coil used in a composite resonator [26].…”
Section: Discussionmentioning
confidence: 76%
“…The unification of proton-MRI and EPRI, called coregistration electron paramagnetic resonance/nuclear magnetic resonance (EPR/NMR) imaging, requires technological advances in magnets, RF coils, and software [8,9]. Sato et al [1] reported their EPR/NMR imaging instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Since an electron spin system has an extremely short relaxation time compared to that of a nuclear spin system, most EPR imaging uses a continuous-wave (CW) detection protocol. While time-domain EPR spectroscopy and imaging at frequencies below 1 GHz are available for animal experiments at some laboratories [12][13][14], EPR imaging still requires CW-EPR instruments for paramagnetic materials with broader EPR absorption spectra.…”
Section: Introductionmentioning
confidence: 99%
“…One way to get around this is to perform a CT or MR image of the same subject under identical posture, so that one can co-register spin distribution and the related anatomical features. Attempts have been made to co-register EPRI with MRI, 122,123 OMRI with BOLD-MRI etc. Such co-registration strategies will be very useful in the unambiguous interpretation of physiology.…”
Section: Recent Developments and Future Directionsmentioning
confidence: 99%